Morphological Features of Wound Canals and Intracranial Pathology in Non-Penetrating Gunshot Craniocerebral Injuries - Altabrouri, M.S.; Usatov, S.A. (TERRA ORTHOPAEDICA, 2023)
Background. Non-penetrating craniocerebral trauma in modern warfare, according to our data, accounts for up to a fifth of all gunshot wounds of the skull and brain in armed conflicts at the end of the last century and the beginning of the current century. It is a complex problem of military field surgery, first of all from the point of view of solving an important task of the medical services of the warring parties – restoring the maximum number of wounded. The study of pathomorphological wound channels in various types of gunshot non-penetrating craniocerebral injuries gives opportunities for the development of adequate options for access during surgical treatment. Object: to reveal the morphological features of wound canals and internal cranial injuries in gunshot non-penetrating craniocerebral injuries for optimal planning the primary surgical treatment of the wound. Material and Methods. Study and analysis of morphological features of wound canals and intracranial pathology in 155 non-penetrating gunshot craniocerebral injuries of the military who underwent surgical treatment in the 2nd and 3rd level healthcare institutions during the war in 2014-2020. The morphology of wound canals and intracranial injuries were studied based on the laws of wound ballistics, clinical data, and computed tomography data. Results. The largest proportion of non-penetrating gunshot wounds is perforated and depressed fractures (39.9%); perforated fractures with penetration of a fragment to the inner plate of the bone account for 20% and incomplete (to the bone) make up 5.8%. Among blind non-penetrating wounds, single ones prevail (65.2%). More often, they have a cylindrical blind canal. Subarachnoid hemorrhage, brain congestion, and very rarely epidural hematoma (one case) are found in almost all perforated bone fractures. A more complex pathomorphological structure is present in multiple non-penetrating gunshot wounds. At the same time, only one fragment causes a depressed skull fracture. Large and small wound canals can be distinguished by width. The latter do not damage the bones and do not require surgical treatment. This type of injury is accompanied by a subarachnoid hemorrhage in 78% of cases and by brain congestion near the fracture in 43% of cases. Tangential injuries occur in 21.9% of injuries; they have a grooved elongated shape. The bottom of these wounds are linear and compressed fractures. Rarely, subdural and intracerebral hematomas are formed in the projection of the fracture. All non-penetrating injuries are accompanied by small brain congestion of the I-II degrees and subarachnoid hemorrhage. Epidural and intracerebral hematomas can rarely occur with blind non-penetrating cranial injuries. Conclusions. Non-penetrating multiple fragmental injuries are accompanied by the greatest soft tissue damage. In case of blind wound canals, there are incomplete perforated and perforated-depressed skull fractures; linear and depressed fractures occur in tangential canals. Regardless of the type of wound canals in the brain, there are small congestions (hemorrhages) and subarachnoid hemorrhage. In rare cases, epidural and intracerebral hematomas are formed. Subdural hematomas, sometimes combined with intracerebral hematomas, are found in tangential non-penetrating wounds. Projectiles in tangential wounds do not cause molecular shock and do not lead to secondary necrosis, therefore, it is not necessary to cut the edges of the wound during the primary surgical treatment.